Investigation of the structure-property relation for graphene oxide based acrylonitrile butadiene styrene nanocomposites - Mohammadsalih, Zaid G.; Sapuan, S.M. (Taylor and Francis, 2024)
The improvement of the structure-property relation in nanocomposites between different polymer matrices and the embedded nano-additives has become a strategic blueprint for many academic counterparts around the globe. In this work, different loadings of graphene oxide (GO) varied from 1.0 to 3.0 wt. % were mixed with acrylonitrile butadiene styrene (ABS) using solution casting approach. The resulted nanocomposites underwent to spectral, structural, morphological, mechanical, thermal and thermomechanical tests. Different kinds of instruments associated with each test were employed to draw a professional conclusion about the potential improvement in structure-property relation. The targeted improvement was achieved as spectral, structural and morphological investigations confirmed the interaction, structural variation, and good dispersion of GO in ABS; respectively. Furthermore, as GO loadings went higher, the mechanical, thermal, and thermomechanical performances for the nanocomposites were improved compared to the neat polymer. Young’s modulus, tensile strength, thermal decomposition, and visco-elastic properties showed an enhancement compared to the neat polymer. The mechanical and thermomechanical performances for the nanocomposites recorded significant promotions.